2012
DOI: 10.1080/08985626.2010.535856
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneur political skill and new venture performance: Extending the social competence perspective

Abstract: Research on the social competence perspective holds that since operating high performing new ventures is dependent on entrepreneurs' ability to influence stakeholder actions, entrepreneur social competence is likely critically important to new venture performance. Using a sample of 163 entrepreneurs throughout the USA, we extend such research by examining the entrepreneur political skill new venture performance relationship. Our results suggest that political skill, which is the component of social competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 86 publications
(190 reference statements)
2
62
0
4
Order By: Relevance
“…Leadership effectiveness includes various aspects of leadership outcomes, such as organizational performance, managerial performance, and follower attitudes and job performance (DeRue et al 2011;Ewen et al 2013;Tocher et al 2012). Leadership effectiveness includes various aspects of leadership outcomes, such as organizational performance, managerial performance, and follower attitudes and job performance (DeRue et al 2011;Ewen et al 2013;Tocher et al 2012).…”
Section: Political Skill and Leadership Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership effectiveness includes various aspects of leadership outcomes, such as organizational performance, managerial performance, and follower attitudes and job performance (DeRue et al 2011;Ewen et al 2013;Tocher et al 2012). Leadership effectiveness includes various aspects of leadership outcomes, such as organizational performance, managerial performance, and follower attitudes and job performance (DeRue et al 2011;Ewen et al 2013;Tocher et al 2012).…”
Section: Political Skill and Leadership Effectivenessmentioning
confidence: 99%
“…Other studies have directly examined and confirmed a positive relationship between political skill and leader effectiveness, as measured by perceived organizational support (Treadway et al 2004), work unit performance, leader performance (Brouer et al 2013;, follower effectiveness (Brouer et al 2013), team performance (Ahearn et al 2004), overall firm performance and entrepreneurial performance (Tocher et al 2012). Semadar et al (2006) compared the predictive effectiveness of political skill with other social effectiveness constructs (self-monitoring, leadership selfefficacy, and emotional intelligence), and found that political skill was the only significant contributor.…”
Section: Political Skill and Leadership Effectivenessmentioning
confidence: 99%
“…Individual characteristics such as political skill are suggested to help entrepreneurs shape and build resource‐rich social networks, which, in turn, provide social capital critical for desirable venture performance (Baron, ; Baron and Markman, ; Tocher et al., ). This suggestion aligns with recent findings that entrepreneurs' networking strategies influence the creation and development of resource‐rich networks; that is, strategies such as networking orientation in building potentially valuable ties (Ebbers, in press), participation in heterogeneous industry events or bridging between events with few common participants (Stam, ), network‐broadening and network‐deepening networking styles (Vissa, ), and catalysing strategies for efficient tie formation (Hallen and Eisenhardt, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Simultaneously, a recent study of the association of political skill and venture performance focuses on political skill as an individual characteristic that may influence how entrepreneurs construct and use their social networks (Tocher et al., ). Although highly correlated with social skill, political skill is more widely studied in organizational settings and refers to ‘the ability to effectively understand others at work and use such knowledge to influence others to act in ways that enhance one's personal and/or organizational objectives’ (Ferris et al., , p. 127).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…objective of seeking to get insight into the role of political skill in the organizational variables that influence performance (Brouer et al, 2015;Harris et al, 2007;Tocher et al, 2012;Wihler et al, 2017). This study seeks to conceptually investigate the intricate relationship between social networks, tacit knowledge, and innovation in influencing the role of political skills in entrepreneurship education.…”
mentioning
confidence: 99%